Criminalizing Coerced Submission in the Workplace and in the Academy - Buchhandler-Raphael, Michal (Columbia Journal of Gender and Law, 2010)
This Article challenges the prevailing view that Title VII and Title IX provide a single conceptual model that fit all forms of sexual harassment. In particular, it questions the assumption that coerced sexual intercourse in the workplace and in the academy is merely another form of sexual harassment that can be addressed within the current legal framework. Rather, the current paradigm must be critically revisited in order to provide an alternative account of these “submission cases” that separately categorizes them and acknowledges their distinctive harms. Accordingly, this Article suggests that these cases should be criminalized, and elaborates upon the justifications and policy goals that support this choice and make it a desirable remedy. This Article further explores the practical ramifications of an alternative account by examining which criminal model is better suited to criminalize coerced submission. Comparing and contrasting a lack of consent model and a sexual coercion model, the Article hypothetically applies them to various cases that were litigated under the sexual harassment framework. This exercise demonstrates that the sexual coercion model provides a more comprehensive and pragmatic construct for criminalization. Therefore, this Article proposes the adoption of a specialized criminal statute based on the sexual coercion model that would criminalize supervisory sexual abuse of power within the workplace and the academy and identify several conditions that suggest that submission resulted from this abuse. Such a proposal would carefully target sexually abusive situations that may be plausible candidates for criminalization and offer a narrowly crafted prohibition that is both gender-and race-neutral and limited in scope to avoid over-criminalization.